Divide this polynomial.

Algebra Level 4

Suppose there exists a polynomial p(x) , which when divided by ( x -1) gives a remainder -1 , when divided by ( x -2) gives a remainder 3 and when divided by ( x +3) gives a remainder 4. Let r(x) be the remainder when that polynomial is divided by ( x -1) ( x -2) ( x +3) . Find the value of r(20) +2.9 .


The answer is 437.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Daniel Liu
Apr 8, 2014

From the first few conditions, we know that p ( 1 ) = 1 p(1)=-1 , p ( 2 ) = 3 p(2)=3 , and (p(-3)=4).

The second part tells us that p ( x ) = ( x 1 ) ( x 2 ) ( x + 3 ) Q ( x ) + r ( x ) p(x)=(x-1)(x-2)(x+3)Q(x)+r(x) . We know that deg ( r ( x ) ) = 2 \text{deg}(r(x)) =2 because deg ( ( x 1 ) ( x 2 ) ( x + 3 ) ) = 3 \text{deg}((x-1)(x-2)(x+3))=3 . Therefore, r ( x ) = a x 2 + b x + c r(x)=ax^2+bx+c .

Plugging in the values x = 1 , 2 , 3 x=1,2,-3 in p ( x ) = ( x 1 ) ( x 2 ) ( x + 3 ) Q ( x ) + a x 2 + b x + c p(x)=(x-1)(x-2)(x+3)Q(x)+ax^2+bx+c gives p ( 1 ) = a + b + c = 1 p(1)=a+b+c=-1 p ( 2 ) = 4 a + 2 b + c = 3 p(2)=4a+2b+c=3 p ( 3 ) = 9 a 3 b + c = 4 p(-3)=9a-3b+c=4

Solving the system of equations, we arrive at the conclusion that a = 21 20 a=\dfrac{21}{20} , b = 17 20 b=\dfrac{17}{20} , and c = 29 10 c=-\dfrac{29}{10}

Therefore, r ( 20 ) + 2.9 = 21 20 ( 20 ) 2 + 17 20 ( 20 ) 29 10 + 2.9 = 437 r(20)+2.9=\dfrac{21}{20}(20)^2+\dfrac{17}{20}(20)-\dfrac{29}{10}+2.9=\boxed{437} .

Nice!

Finn Hulse - 7 years, 2 months ago

But why can't r(x) be a linear polynomial or a constabt one?

Adarsh Kumar - 7 years, 1 month ago

Log in to reply

If it is linear, solving the system of equation will give a = 0 a=0 .

Shaun Loong - 6 years, 10 months ago

General format for r(x) is ax^2+bx+c. Yes, r(x) can be linear or a constant, if r(x)=0, then a=0 and if r(x)=c (Constant) then a=b=0.

Venkata Karthik Bandaru - 6 years, 3 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...